A Study to Assess the Correlation Between Smart Phone Use Addiction with Text Neck Syndrome and Hand Discomfort Among the Adult Students in Saveetha University - Dr.Mrs.Bhuvaneshwari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The smart phone is the most popular device used among the adults. Smart phone addiction is the most common phenomenon that pertains to be common among the smart phone user The incidence of musculoskeletal disorders (MSD) of hand, wrist, forearm, arm and neck has been increasing all over the world due to prolonged; forceful, low amplitude, repetitive use of hand held devices(HHD) such as computer, laptops, smart phones, tablets, etc.,. continuous repetitive use of movements in the hand Methods A descriptive research design was done in saveetha university .100 adult students are included in our study. Purposive sampling method was used in selecting the samples. Structured interview by using Smart Phone Addiction scale, Cornell Hand Discomfort Questionnaire (CHDQ), Neck Disability Index (NDI), were used to collect the data smart phone addiction, hand discomfort and neck disability. Results There is more number of females 52% than males 48%. Mean ±SD of SAS, NDI and CHDQ are 106±34, 19.74 ± 6.8 and 46.2 ± 57. Spearman rank correlation coefficient shows a significant moderate positive correlation between SAS and NDI ( r = 0.651, p =< 0.001), and between SAS and CHDQ ( r = 0.541, p = <0.001).